Variasi Verba “Memasak” Dalam Bahasa Bali - Ni Luh Putu Puspita Agustini (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2022)
This paper describes the meaning of the verb cook in Balinese based on the theory of Natural Semantic Metalanguage. This research is to obtain a comprehensive meaning configuration of the lexical verb